2022
DOI: 10.3390/su142215288
|View full text |Cite
|
Sign up to set email alerts
|

How the Education Industries React to Synchronous and Asynchronous Learning in COVID-19: Multigroup Analysis Insights for Future Online Education

Abstract: The phenomenon of the COVID-19 pandemic requires prevention actions, such as social and physical distancing. In education, there is no choice but to adapt to online learning from traditional face-to-face learning. Online learning is divided into two approaches, namely synchronous and asynchronous learning. In practice, both synchronous and asynchronous learning have their respective advantages and disadvantages that can affect the efficiency and the effectiveness of online learning that are felt by students. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Differences between synchronous and asynchronous learning may be partially explained by differences in how instructors seek out student acceptance of the formats. Synchronous learning acceptance is influenced by technological innovations and quality of the learning system, while asynchronous learning acceptance is influenced by organizational and technical support, technological innovations-however, both forms of acceptance are strongly influenced by the characteristics of the teachers (Persada et al, 2022). Perhaps unifying the aforementioned fields, some research has also shown that asynchronous collaboration is most effective when coupled with synchronous forums, such as in the case of oral learning skills in EFL classes (see Fischer & Yang, 2022), or in the learning outcomes for math students during the COVID lockdowns (Calder et al, 2021).…”
Section: Commonly Used Communication Methods and Their Importancementioning
confidence: 99%
“…Differences between synchronous and asynchronous learning may be partially explained by differences in how instructors seek out student acceptance of the formats. Synchronous learning acceptance is influenced by technological innovations and quality of the learning system, while asynchronous learning acceptance is influenced by organizational and technical support, technological innovations-however, both forms of acceptance are strongly influenced by the characteristics of the teachers (Persada et al, 2022). Perhaps unifying the aforementioned fields, some research has also shown that asynchronous collaboration is most effective when coupled with synchronous forums, such as in the case of oral learning skills in EFL classes (see Fischer & Yang, 2022), or in the learning outcomes for math students during the COVID lockdowns (Calder et al, 2021).…”
Section: Commonly Used Communication Methods and Their Importancementioning
confidence: 99%
“…Integrating interprofessional education, preventive medicine, and early intervention strategies can foster a holistic understanding of healthcare among students. Furthermore, leveraging innovative teaching methodologies, such as problem-based learning, simulation, and digital technologies, can help engage students and enhance their clinical reasoning and decision-making skills [ 36 ]. By implementing these curricular changes, state medical schools can better prepare graduates for careers in general practice and contribute to a more robust primary care workforce.…”
Section: Potential Solutionsmentioning
confidence: 99%
“…Categorized by temporal constraint, online learning can be roughly divided into two types: asynchronous and synchronous (Persada et al, 2022 ). Asynchronous online learning refers to the acquiring of knowledge by students from online curricular materials on their own time, and thus, the teacher and students remain independent in both time and space (Friend and Johnston, 2005 ; Murphy et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Asynchronous online learning refers to the acquiring of knowledge by students from online curricular materials on their own time, and thus, the teacher and students remain independent in both time and space (Friend and Johnston, 2005 ; Murphy et al, 2010 ). Despite being less constrained by time, asynchronous online learning indicates a higher demand for students' self-discipline due to limited interaction with instructors (Persada et al, 2022 ). Unlike asynchronous online learning, another type, synchronous online learning, requires students and teachers to schedule the same time for spontaneously communicating as if they were physically co-present despite being geographically independent (Murphy et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%